The Role of Sayyidah Aisyah in the Dissemination of Hadith - Karina, Elda; Hanim, Alisha Nur Lathifah; Diva, Eria Fara (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine the role of Sayyidah Aisyah (R.A.) in the dissemination of hadith among the Muslim community. The primary focus of the research is to understand Aisyah’s contributions as one of the main transmitters of the sayings and actions of the Prophet Muhammad (PBUH), as well as her role as a teacher to the Prophet’s companions and the succeeding generations.The method used in this study is library research, collecting data from various sources such as historical books, scholarly articles, and related documents. The findings show that Sayyidah Aisyah played a crucial role in spreading religious knowledge, particularly hadith. Key findings include Aisyah’s ability to explain Islamic teachings and issue legal rulings (fatwas), making her an important reference for the Muslim community.Moreover, Aisyah was actively involved in educating the Prophet’s companions and subsequent generations, many of whom studied directly under her guidance. Her contributions extended beyond her lifetime, continuing to influence the development of hadith sciences and Islamic understanding within the Muslim world up to the present day.This research affirms that Sayyidah Aisyah’s role in the transmission of hadith is highly significant, and her impact is still evident in contemporary Islamic scholarship. Thus, Aisyah was not merely the wife of the Prophet, but also a key figure in the history of Islamic teaching and dissemination.